New species of deep-sea Heteropolypus soft corals (Anthozoa: Octocorallia) from the Kurile Islands, Sea of Okhotsk (Northwest Pacific), with summary data on distinctive characters of the known species of the genus - Dautova, Tatiana N. (European Journal of Taxonomy, 2022)
The present paper records two new species of deep-sea soft corals, Heteropolypus annae sp. nov. and H. roseus sp. nov., from the area of the Kurile Islands, Sea of Okhotsk, Northwest Pacific. Distinctive characters for each new species are provided and depicted with scanning electron microscopy imaging. The present finding of previously undescribed species emphasizes the need for further surveys, particularly in deeper waters in the area to improve knowledge of the deep-sea Octocorallia fauna in the Far East seas. The distribution of species of Heteropolypus in the temperate Northwest Pacific and their taxonomy characters are discussed based on the published literature and own data. A modified diagnosis of the genus is proposed.